2013
DOI: 10.1093/neuonc/not232
|View full text |Cite
|
Sign up to set email alerts
|

A disintegrin and metalloproteinases 10 and 17 modulate the immunogenicity of glioblastoma-initiating cells

Abstract: Therefore, ADAM10 and ADAM17 constitute suitable targets to boost an immune response against GIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 34 publications
(51 reference statements)
3
49
0
Order By: Relevance
“…Wolpert et al demonstrated that NKG2dL mRNA and surface expression levels may differ, which is most likely due to posttranslational and posttranscriptional modification (69). Other mechanisms, including the induction of surface loss of MIcB via the secretory pathway by human cytomegalovirus, may also serve a role (70,71) in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Wolpert et al demonstrated that NKG2dL mRNA and surface expression levels may differ, which is most likely due to posttranslational and posttranscriptional modification (69). Other mechanisms, including the induction of surface loss of MIcB via the secretory pathway by human cytomegalovirus, may also serve a role (70,71) in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Increased Acts as a sheddase for membrane-bound molecules such as N-CAM (Kohutek et al 2009), CD44 (Murai et al 2004), L1CAM (Mohanan et al 2013), CXCL16 (Ludwig et al 2005), and Coxsackievirus and Adenovirus Receptor (CAR) (Houri et al 2013), thereby promoting glioma motility and growth; important for the renewal of glioma stem-like cells (Bulstrode et al 2012); involved in the impaired immune recognition of glioma stem cells (Wolpert et al 2014). …”
Section: Adam10mentioning
confidence: 99%
“…Ambiguous data Decreased expression reported by Comincini et al (2009), increased according to TCGA data; mediates hypoxia-induced glioma invasiveness (Zheng et al 2007); may contribute to stemness maintenance through the Notch signaling ); promotes the malignant phenotype of glioma cells ); introduction into astrocytes induced a neoplastic phenotype by deregulating EGFR signaling ); involved in the impaired immune recognition of glioma stem cells (Wolpert et al 2014). …”
Section: Adam17mentioning
confidence: 99%
See 1 more Smart Citation
“…This also causes a release of trophic factors to stimulate tumor growth, dispersal, and modulation of inflammatory responses. Members of the A Disintegrin and Metalloproteinase (ADAM) family of zinc-dependent proteinases contribute to GBM therapeutic resistance and invasiveness (15,16), as well as to the regulation of GSCs (17)(18)(19). ADAMDEC1 is a soluble member of this family that is novel in mammals.…”
Section: Introductionmentioning
confidence: 99%